Prognostic Factors and Surgery for Breast Cancer Patients With Locoregional Recurrence: An Analysis of 5,202 Consecutive Patients - Huang, Jiahui; Tong, Yiwei; Chen, Xiaosong; Shen, Kunwei (Frontiers in Oncology, 2021)
Purpose. With the application of 'less extensive surgery' in breast cancer treatment, the pattern of locoregional recurrence (LRR) has significantly changed. This study aims to evaluate the risk and prognostic factors of LRR in recent large breast cancer cohort. Methods. Consecutive early breast cancer patients who received surgery from January 2009 to March 2018 in Shanghai Ruijin Hospital were retrospectively analyzed. LRR was defined as recurrence at the ipsilateral breast (IBTR), chest wall or regional lymph nodes and without concurrent distant metastasis (DM). Patients' characteristics and survival were compared among these groups. Results. Among 5202 patients included, 87 (1.7%) and 265 (5.1%) experienced LRR and DM as first event after a median 47.0 (3.0-122.5) months follow-up. LRR were significantly associated with large tumor size and positive lymph node status (P < 0.05). Forty (46.0%) patients received further salvage surgery after LRR and had a significantly better 3-year post-recurrence overall survival than those did not (94.7% vs 60.7%, P=0.012). Multivariate analysis showed that salvage surgery for LRR was independently associated with better survival (HR=0.12, 95% CI 0.02-0.93, P=0.043) along with ER positivity (HR=0.33, 95%CI 0.12-0.91, P=0.033). Conclusion. LRR rate was relatively low in recent era of breast cancer treatment. Tumor size and lymph node status were associated with risk of LRR and salvage surgery for selected LRR patients achieved an excellent outcome.